Some new insights on the interindustry wage structure from the German Socioeconomic Panel - Michael C. Burda (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1991)
This paper investigates the interindustry wage structure in the 1985 wave of the German Socioeconomic Panel. In addition to the usual controls, this survey contains detailed inf ormation on job characteristics and work conditions. Interaction of industry affiliation is significant with several individual attributes, especially job tenure; homogeneity of earnings equations across these attributes is decisively rejected. The industry wage structure is insignificant for workers with low job tenure. These results are consistent with the interpretation of interindustry wage differentials as shared rents from industry or firm-specific human capital.
Keywords: 330